Exposure to Air Pollution and Risk of Cancer in Children- A Case Control Study - Mazloumi Tabrizi, Maral; Hosseini, Seyed Ahmad; Akbarzadeh Khiyavi, Azim (Asian Pacific Journal of Cancer Biology, 2017)
Introduction: Children are one of the easiest affected group from environmental deterioration and detrimental factors, Due to their biological and behavioral differences. And childhood cancer has considered as one of the most common cause of death in children in developing countries. Exposure to some environmental factors during childhood can increase the risk of cancer in the offspring. Methods: This study aimed to evaluate the role of living in the pollutant regions and exposure to cigarette or hookah smoke on the incidence of cancer in children. This case-control study was considered 22 cases and 100 controls, under 10 years, who was born and lived in pollutant regions of Tehran in 2014-2015. Results and Disscotion: Regarding the important risk factors: familial background of underlying diseases or cancer. However, in this ages, the Familial background of cancer is considered as the most crucial risk factor of the incidence of cancer in children (P=0.000, OR=7.639, CI 95% 4.230-13.794). Moreover, the second most significant item is live in regions with polluted air (P=0.019, OR=4.222, CI 95% 1.172-15.211).